A bio-inspired polarization navigation sensor based on artificial compound eyes. (1st July 2022) - Liu, Jianying; Zhang, Ran; Li, Yahong; Guan, Chuanlong; Liu, Rui; Fu, Jiaxin; Chu, Jinkui
Abstract: Insect compound eyes are optical systems with small volume and a compact structure. The ommatidia in the dorsal rim area of some insects have polarized vision, which can perceive the polarization pattern of the sky and provide them with navigation information. In this paper, inspired by the polarization-sensitive compound eyes of insects, a bio-inspired polarization navigation sensor based on artificial compound eyes is designed. The sensor consists of an artificial compound eye, an integrated polarization detector and an integrated circuit. The optical path of the sensor uses the lens defocus method, which can ensure that the sensor obtains redundant polarization information. The integrated polarization detector is used to obtain the polarization information of the incident light, and the integrated circuit is responsible for the calculation. To extract effective information from images, we propose a multi-threshold segmentation method to filter and classify effective pixels. We use the least squares method to fit the inherent error of the sensor and then compensate it. The indoor calibration accuracy of the sensor is ±0.3°, and the outdoor calibration accuracy is ±0.5°. The sensor can provide accurate direction information for general smart mobile devices. The size of the sensor is 4 × 4 × 2 cm, and the weight is only 15 g. The key components of the sensor can be mass-produced, and it is a miniaturized and low-cost polarization navigation sensor.